INFORMATION AND COMMUNICATION PEDAGOGICAL ENVIRONMENT AS MEANS OF FORMING OF MOTIVATION TO PROFESSIONAL ACTIVITY OF PRIMARY SCHOOL TEACHERS - Onishchenko І.В. (Journal of Information Technologies in Education (ITE), 2015)
In terms of education informatization the formation of motivation to professional activity of the future primary school teacher most effectively takes place in information and communication pedagogical environment that provides new ways of presenting information, promotes the development of needs and readiness of students to perform professional activities with application of information and communication technologies. Information and communication pedagogical environment is a complex, multi-element pedagogical system, which accumulates information, organizational, intellectual, methodological, technical, program resources and promotes information and educational interaction in the model «teacher – student – environment». This environment creates favorable terms for forming of the expressed interest in the profession of primary school teacher, motivational-valued attitude toward pedagogical activity, promotes the education of students in information and pedagogical culture and creative activity in the independent capture of professional disciplines. Forming of interest in the profession of primary school teacher is assisted by bringing in of future specialist to the creative searches by the decision of the research tasks, creative nature, creation of own electronic products, creative projects. Information and communication pedagogical environment provides the realization of the potential of students by bringing them to self-education, which in terms of the environment acquires creative and research direction and promotes for non-standard decision of professional tasks on innovative bases.